2013
DOI: 10.1002/jhm.2063
|View full text |Cite
|
Sign up to set email alerts
|

Choosing wisely in adult hospital medicine: Five opportunities for improved healthcare value

Abstract: BACKGROUND In an effort to lead physicians in addressing the problem of overuse of medical tests and treatments, the American Board of Internal Medicine Foundation developed the Choosing Wisely campaign. The Society of Hospital Medicine (SHM) joined the initiative to highlight the need to critically appraise resource utilization in hospitals. METHODS The SHM employed a staged methodology to develop the adult Choosing Wisely list. This included surveys of the organization's leaders and general membership, a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
119
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 49 publications
0
119
0
Order By: Relevance
“…In conclusion, there are critical demands for health care cost containment and quality improvement (4)(5)(6)(7)(8). Establishing laboratory acceptance criteria for viral NAAT of CSF samples is one example of an approach to both reducing costs and improving patient care by reducing unnecessary testing and its associated consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, there are critical demands for health care cost containment and quality improvement (4)(5)(6)(7)(8). Establishing laboratory acceptance criteria for viral NAAT of CSF samples is one example of an approach to both reducing costs and improving patient care by reducing unnecessary testing and its associated consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Some have speculated that the presence of a VIP patient may be disruptive to the care of non-VIP patients, while others have cautioned physicians about potential dangers to the VIP patients themselves. [4][5][6] Despite much being written on the topics of VIP patients and services in both the lay and academic press, our literature review identified only 1 study on the topic, which cataloged the preferential treatment of VIP patients in the emergency department. 6 We are unaware of any investigations of VIP-service use in the inpatient setting.…”
mentioning
confidence: 99%
“…We adapted an existing framework developed on the basis of evidentiary rationales identified in a review of 25 societies' Choosing Wisely lists 10 and considered criteria used by other societies [11][12][13] and guidance provided by Choosing Wisely Canada.…”
Section: Criteria For Recommendation Selection and Prioritizationmentioning
confidence: 99%